Expression of the Gs protein alpha-subunit disrupts the normal program of differentiation in cultured murine myogenic cells. - Tsai, C C (1997)
The manner in which growth factors acting at the cell surface regulate activity of myogenic basic-helix-loop-helix proteins in the nucleus and thus control the fate of committed skeletal myoblasts remains poorly understood. In this study, we report that immunoreactive Gs protein alpha-subunits (Gs alpha) localize to nuclei of proliferating C2C12 myoblasts but not to nuclei of differentiated postmitotic C2C12 myotubes. To explore the biological significance of this observation, we placed a cDNA encoding Gs alpha in an expression vector under the control of a steroid-inducible promoter and isolated colonies of stably transfected C2C12 myoblasts. Dexamethasone-induced expression of activated Gs alpha markedly delayed differentiation in comparison with uninduced stably transfected cells, which differentiated normally in mitogen-depleted media. Northern blot analysis showed that impaired differentiation was associated with delayed up-regulation of MyoD and myogenin and delayed down-regulation of Id, a dominant negative inhibitor of differentiation. Similar impairment of differentiation could not be reproduced in wild-type C2C12 cells by increasing intracellular cAMP either with forskolin or treatment with a cell-permeable cAMP analog. However, treatment of myoblasts with cholera toxin markedly inhibited myogenic differentiation. Taken together, these findings suggest a novel role for Gs alpha in modulating myogenic differentiation.